2021
DOI: 10.1021/acs.orglett.1c02369
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Catalyzed in Situ Denitrogenative Sulfonylation of Sulfonylhydrazones

Abstract: A photocatalyzed in situ denitrogenative sulfonylation of N-arylsulfonyl hydrazones has been developed. This transformation provides a low-carbon strategy to assemble arylalkyl sulfones in a stepwise denitrogenation/sulfonylation manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…in Scheme 4. The influence of the electron density of the Naryl moiety on the protocol's outcome was tested (37)(38)(39)(40)(41), revealing that electron-rich phenyl rings led to slightly low yields (38 and 41). The heteroaryl functionality of glycinate was successfully introduced using this procedure (42).…”
Section: Resultsmentioning
confidence: 99%
“…in Scheme 4. The influence of the electron density of the Naryl moiety on the protocol's outcome was tested (37)(38)(39)(40)(41), revealing that electron-rich phenyl rings led to slightly low yields (38 and 41). The heteroaryl functionality of glycinate was successfully introduced using this procedure (42).…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Xie, Zeng, and co-workers introduced a photocatalytic method for synthesizing aryl or alkyl sulfones 106.2 (Scheme 106). 237 It was found that aryl or heteroaryl-substituted sulfonylhydrazones 106.1 worked well in this transformation. Similarly, sulfonylhydrazones derived from acetophenone, benzophenone, and benzocycloketone were also proven to be capable substrates (106.3−106.8).…”
Section: N-tosylhydrazonesmentioning
confidence: 98%
“…In this regard, substantial progress in metal carbenoid intermediates has been demonstrated by the groups of Yu, 41 Valdés, 42 and Zhao 43 using catalysts based on transition metals, such as copper and iron, to access aryl alkyl sulfones via denitrogenation of tosylhydrazones (Scheme 1b, top). More recently, a photocatalytic strategy using an Ir catalyst 44 has been developed to achieve denitrogenative sulfonylation of tosylhydrazones to furnish aryl alkyl sulfones (Scheme 1b, bottom). The proposed intermediate of the reaction, a carbene radical cation generated from carbene by a photooxidant, is an elusive intermediate due to the higher electrophilicity of the carbene intermediate.…”
Section: Introductionmentioning
confidence: 99%